Pengaruh Gaya Kepemimpinan Lurah Tempe Terhadap Kepuasan Masyarakat Di Kantor Kelurahan Tempe Kabupaten Wajo - Syupriadi Mujibu; Eka Patmasari; Andriani Andriani (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
This study aims to determine how much influence the leadership style of the Tempe village head has on community satisfaction at the Tempoe Village Office, Wajo Regency, using survey research, namely only a portion of the population is used as a sample. The population in this study were 174 people, then the Sloavin formula was used to determine the sample and to produce a sample of 64 people, the sample used was random sampling (simple random sample). Data collection techniques using observation, questionnaires and documentation. For data analysis techniques used are quantitative descriptive analysis techniques and quantitative associative analysis techniques. The benefits of this research are practical and theoretical benefits, 1. The practical benefits of this research are: As an evaluation of leadership style and employee service satisfaction and as input for employees, 2. The theoretical benefits of this research are: it is hoped that it can be used as material for further study relevant and study material towards developing the concept of organizational climate and employee work ethic. The results showed that there was a positive influence of leadership on community satisfaction in the Tempe Village Office, Wajo Regency.